The Political Economy Of Constitutional Reform In An Externally-Constrained Environment: China’s Shadow Over Hong Kong And Strategies To Minimise It - Mushkat, Miron; Mushkat, Roda (Journal of Malaysian and Comparative Law, 2003)
Hong Kong is a highly developed metropolis - affluent, dynamic, flexible, open, blessed with excellent infrastructure, enjoying British-style rule of law, benefiting from a free flow of information, and being "guided" by a generally efficient and clean government. Its economic foundations are robust and their social counterparts display few signs of fragility. Hong Kong's political institutions, on the other hand, still bear the marks of the benevolent authoritarianism which characterized the colonial era. As such, they are arguably out of sync with the socio-economic environment in which they are embedded. A distinct majority of the local population is clamoring for representative democracy. Those spearheading the effort have exhibited remarkable courage, dedication, selflessness, and consistency. However, they may have pursued an overly narrow agenda. This agenda could be broadened and, in the process, possibly rendered more palatable from a Chinese perspective, as well as intellectually credible.